The Effectiveness of Problem-Based Learning and Digital Media-Assisted Discovery Learning on the Ability to Listen to Persuasive Texts Reviewed from the Learning Style of Junior High School Students - Pujiastuti, Indriani Diah Eko; Naryatmojo, Deby Luriawati (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The ability to listen to persuasive texts is one of the important language skills to be developed in junior high school students because it is related to the ability to understand, interpret, and evaluate the messages received. However, listening learning in schools still tends to be conventional and does not make optimal use of digital media, resulting in low student involvement in the learning process. This study aims to analyze the effectiveness of Problem-Based Learning (PBL) and Discovery Learning assisted by digital media on the ability to listen to persuasive texts reviewed from the learning style of junior high school students. The research uses a quantitative approach with quasi experiment methods and 2×2 factorial design. The research subjects consisted of grade VIII students who were grouped based on learning models and learning styles. Data were collected through listening ability tests, learning style questionnaires, observations, and documentation, then analyzed using descriptive statistics and Two-Way ANOVA. The results of the study showed that PBL assisted by digital media was more effective than Discovery Learning and conventional learning in improving the ability to listen to persuasive texts. In addition, learning styles affect learning outcomes and there is a significant interaction between learning models and student learning styles. This study confirms that the integration of active learning models and digital media can improve the quality of listening learning in a more adaptive and contextual manner.